Finite element analysis of concrete shell using ansys software - Siti Zulaikha, Mohamad Amin (2013)
This research deals with the design of concrete shell structure based on finite element method using ANSYS software. Concrete shell is a very thin shell but very strong structure. There are many researches done to analyze concrete shell using finite element method. From the researches, all the steps of calculation that included formulas to analyze the concrete shell can be found. Using ANSYS software has resulted in considerable advances in the analysis and design of any structures. While by determining the design of concrete shell using Finite Element Analysis Method with the use of matrix equations consist of global displacement matrix and also strain displacement matrix. Because all of these methods are based on simplified analysis, they cannot provide the engineer with all the desired design information and only provide the engineer with all the desired design information and only provide very limited indications. Concrete shells have lots of different type of shapes which are folded plate, spherical domes and translation shell. To analyze the design of the concrete shell, ANSYS software will be used. The software consists of three stages of design process. The first stage is preprocessing which the steps of defining the problem that included define the material, element type, shell vertex, shell properties and geometry and also meshing the model. The second stage is solution. In this stage, it will be assigning loads, constraint and solving consists of specifying the load such as point and pressure, constraint the translational and rotational and finally solve the resulting set of equations. The third stage is postprocessing where it is further processing and viewing of the results. In this stage one may wish to see the shell reinforcement design, analyze the deflection, stress and strain of the model. The materials for the concrete shell are concrete and reinforcing steel.